Diagnose foliar em cafeeiro de sequeiro e irrigado na região do alto Paranaíba com o uso do DRIS - Campos, Rodrigo de Arruda (2009)
Cerrado soils have low fertility and under-dosing of fertilizers leads to nutritional imbalance on coffee plantations. This study aimed to: comparatively characterize the main deficiencies, nutritional imbalances and excesses in the aerial part of coffee plant; indicate nutrients which respond well to fertilization and their synergistic and antagonistic interactions; define the critical levels and assess the potential response to fertilization using the DRIS analysis of leaves. The experiment was carried out from 2007 to 2009 in the alto Paranaíba region - Brazil, in cerrado soil. There were selected 59 samples with coffee produced on non-irrigated and 52 on irrigated plantations. With the use of DRIS (The Diagnosis and Recommendation Integrated System) there were defined: a general limitation of macro and micronutrients, levels of sufficiency, Nutritional Balance Index (NBI), Average Nutritional Balance Index (NBIA) and correlation between DRIS indices and concentration of nutrients in leaves. The leaf samples were collected during the phenological phase of buds, removing at random two pairs of leaves from each plant with 20 plants in total. The irrigated coffee showed different response to fertilization than the non-irrigated coffee where Mn (25%) and S (13%) limited the productivity the most. DRIS showed the following nutrients limiting the productivity of non-irrigated coffee: P (18.6%), Fe (15.3%), K = Mn (13.5%) and Zn = B (10.2%). Correlations between DRIS indices allowed the visualization of antagonism and synergism between nutrients, noting that the correlations between N (P, K and S), P (K, Mg and S) and K (Mg and S) were synergistic and the correlations between N (Ca, B, Fe and Zn), P (Ca, B, Fe and Zn) and K (Ca, B, Fe and Zn) were antagonistic. Sufficiency levels estimated by the DRIS index for non-irrigated coffee were: 33-36 g.kg-1 for N, 1.4-1.8 g.kg-1 for P, 46-52 g.kg-1 for K, 11-12 g.kg-1 for Ca, 8-9 g.kg-1 for Mg, 2-3 g.kg-1 for S, 30-42 mg.kg-1 for B, 235-263 mg. kg-1 for Fe, 158-240 mg.kg-1 for Mn and 18-19 mg.kg-1 for Zn. For irrigated coffee the levels were: 30.1 g.kg-1 for N, 1.3 g. kg-1 for P, 22.5 g.kg-1 for K, 7.1 g.kg-1 for Ca, 2.5 g.kg-1 for Mg, 2.2 g.kg-1 for S, 28.3 mg.kg-1 for B, 131.9 mg.kg-1 for Fe, 103.9 mg.kg-1 for Mn, 9.0 mg.kg-1 for Cu, 8.2 mg.kg -1 and for Zn. In the layer of 0-5 cm were: S, P, Ca, Mg and in the layer of 5-20 cm: S, Zn and K. It can be concluded that there is a different sufficiency rate for irrigated and non-irrigated coffee. Presented in descending order are the nutrients which are more likely to respond positively: S> P = Zn> Mg = K = Ca.